Evaluación de seis tipos de abonos orgánicos solidos con diferentes dosis de aplicación en el cultivo de zanahoria (Daucus carotaL.) Durante la época seca en la zona de Quevedo - Toaquiza Masapanta, Vega Lutuala (2011)
In the present searchins was conducted in the dry season in ”La María ” property of the State Technical University from Quevedo (UTEQ), located at km. 7 via Quevedo – El Empalme Los Rios province, under the geographical coordinates 79° 32 ´west longitude and 01° 06´ south latitude, elevation of 120 meters above sea level. The objectives ere to determine the best application rate of six types of solid organic fertilizer in the cultivation of carrots, to establish the the responses of carrot in plant development,with the applications of different organic fertilizers, to determine the dose most responsive the fruit yield, perform economic analysis of treatments in the crop. It was used as the hybrid planting material Figo, studyng such as fertilizers and dose factors “Humus, Bocashi, Compost, chicken manure, cattle manure and swine manure and the high dose, medium and low.” That made up 18 treatments, applied design “randomized complete bloks with 3x6 factorial arrangement with theree replications and use the Tuckey test at 95% chance to establish the difference between the means of treatment.” We evaluated the plant height, bulb diameter, bulb weight, plant mortality, length of bulb yield and economic analysis. Analysis and interpretation of the results concluded: Plant height, diameter of the bulb up to 40 days were not influenced by the types and doses of fertilizer, fertilization with high doses of greater height silver genre that fertilized with low dose The fertilizer influenced the plants height increased to 60 days of culture was pig manure, the application of pig manure at low dose (30 mt / ha) were obtained from fruits of greater diameter, incorporating compost in low dose (30 tm / ha) recorded higher bulb weight, but were influenced in the highest percentage of plant mortality compared to other treatments, the highest average fruit length was achieved with the application of low – dose bokashi (30 tm/ha) Composting of pig manure with low dose had the highest yield per hectare 40888.89 kg / ha and increased net profit and profitability was obtained with pig manure at low dose (30tm/ha), while The total cost was higher in the humus high dose (90tm/ha). They are recommended pig manure in doses (30 tm/ha) in the cultivation of carrots to achieves higher yields and better quality bulbs, use additional doses to corroborate the results obtained in this investigation and thus able to grow carrot organic form of excellent quality and analysis of nematodes prior to planting to prevent an attack, thus guaranteeing the quality of the bulbs.